THE AQUEOUS GEOCHEMISTRY OF GALLIUM, GERMANIUM, INDIUM AND SCANDIUM - Wood S.A.; Samson I.M. (My University, 2006)
Relatively little information is available in the literature regarding the speciation and solubility of Ga, Ge, In and Sc in aqueous solutions, especially at elevated temperatures and pressures. In this paper we critically review stability constants for relevant aqueous complexes of these metals and solubility products for relevant solid phases. Most of the available data refer to standard conditions of temperature and pressure (25 °C and 1 bar), although for Ga and Ge, experimentally derived data are available for some geologically relevant species and phases up to 200–300 °C. The stable oxidation states of the four metals in aqueous solution are Ga(III), Ge(IV), In(III) and Sc(III). The ions of each of these metals are relatively hard in the Pearson [Pearson, R.G. 1963. Hard and soft acids and bases. Journal of the American Chemical Society 85, 3533–3539] sense, forming the strongest complexes with hard ligands such as hydroxide, fluoride, sulfate and phosphate, and weaker complexes with soft ligands such as chloride and bisulfide. The main exception to this rule is In(III), which forms reasonably stable chloride and bisulfide complexes. The hydrated Ga³⁺, In³⁺ and Sc³⁺ ions are all octahedrally coordinated by water molecules, but there is some evidence, e.g., for GaCl4⁻ and InCl4⁻, that a conversion to tetrahedral coordination may occur upon replacement of water by a sufficient number of other ligands.